Re-imagining the environment: using an environmental art festival to encourage pro-environmental behaviour and a sense of place. Issue 3 (3rd March 2016) - Marks, M.; Chandler, L.; Baldwin, C.
Abstract : Environmental art can be used by government as an engaging medium to encourage pro-environmental behaviour and a sense of place at a grassroots level. By stimulating discussion and reflection, environmental art offers an imaginative format to promote environmental engagement. In this case, by placing artworks in nature, a community's focus was drawn to the beauty of their everyday environment and the ideas communicated by the works, in an effort to encourage environmental awareness and stewardship. This study explores audience responses to Floating Land – a local-government-initiated environmental art festival held in the Noosa Biosphere in Australia. A multi-layered perspective of the festival's impact on pro-environmental behaviours and sense of place was investigated via questionnaires administered to the audience, workshop participants and local residents. Data offered insights into attitude differences between those who intended to change their behaviour and those who did not; understandings about the influence of workshop facilitators; and revelations about a community finding opportunities to re-imagine their place through environmental art. Recommendations are offered as a way for governments to incorporate environmental art into their role of educating for the environment. This study contributes to the under-researched area of audience responses to environmental art by providing qualitative and quantitative analysis that draws out understandings of the impact of art that promotes environmental awareness and a sense of place. The study reveals that Floating Land contributed to reinforcing the essential role of local people in engendering positive change, thus manifesting the aims of the Biosphere Reserve and Agenda 21 .